A lithium metal battery electrolyte containing an ammonium-based super polar cation additive
Patent Information
- Application Number
- CN202611044817.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-27
AI Technical Summary
Xiong (Xiong X, et al. Dual-Interface Regulation of Cyclic ThioetherElectrolyte Additives for Enhancing the Cycling Stability of High-VoltageLithium Metal Batteries [J]. Small, 2025, 21, e07802.) 等人提出使用1,4 - 二噻烷(1,4-DH)作为碳酸酯电解液的多功能环硫醚添加剂,可在锂金属负极表面优先吸附并分解,构筑富含LiF与 Li2S的致密SEI膜,显著抑制锂枝晶生长并提高电池整体性能;但1,4-DH添加剂在碳酸酯电解液中的溶解度有限(≤3.0 wt %),且容易在较高电压下发生副反应;Zhang (Zhang L, et al. A fluorine rich borate ionic additive enablinghigh-voltage Li metal batteries[J]. Energy Storage Materials, 2024, 69,103397.)等人报道了一种四(全氟-叔丁氧基)硼酸锂添加剂(LiTFOB),可在锂负极处被还原;其单分子含36个F,因此可生成富含LiF与 Li
B
O的SEI,有效降低电池极化并提升库仑效率;然而该添加剂分子的成本及其用量较高(5.0 wt %),对其后续实际应用有较大限制
(1)本发明所用添加剂中的4-氟苯铵阳离子含有氮与氟元素,带正电且具有较强极性,可快速吸附于锂金属表面,同时其较大的体积可降低溶剂分子在锂负极/电解液界面双电层中的比例,有利于含氮和富含氟元素的SEI形成,并且减少不必要的电解液消耗。
Smart Images

Figure CN122977976A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery electrolytes, and relates to a lithium metal battery electrolyte additive and an electrolyte using the same; specifically, it relates to a lithium metal battery electrolyte containing an ammonium-based strongly polar cationic additive. Background Technology
[0002] The theoretical specific capacity of lithium metal is as high as 3860 mAh g. -1 Far exceeding the 372 mAh g of traditional graphite anode materials -1 This means that lithium anodes have a significant capacity ceiling, offering enormous potential for increasing battery energy density; lithium's electrode potential is -3.04 V (vs. SHE, where SHE is the standard hydrogen electrode), the lowest of all metallic elements. This characteristic enables lithium metal batteries to have higher output voltage and superior power performance, making them suitable for high-power, high-energy-density portable electronic devices and electric vehicles.
[0003] The solvent and lithium salt in the electrolyte are prone to reduction reaction on the surface of the lithium metal anode, which leads to its decomposition and the generation of a series of organic and inorganic products. These products are deposited on the surface of the lithium anode and eventually form a passivation layer covering the surface of the lithium anode, namely the SEI film.
[0004] However, current commercially available electrolyte systems with selenium dendrite (SEI) have defects in composition and structure, leading to problems such as lithium dendrite growth and excessive electrolyte consumption. Typically, spontaneously generated SEIs are mainly composed of organic alkyl lithium, whose inherent brittleness makes them prone to cracking and even shattering. Due to the high reactivity of lithium metal, exposed lithium metal continuously reacts with the electrolyte, resulting in continuous SEI growth and electrolyte consumption. This not only increases the thickness and porosity of the SEI film, leading to increased battery polarization and internal resistance, but also consumes large amounts of lithium metal and electrolyte, reducing the battery's coulombic efficiency. Simultaneously, the continuous damage and regeneration of the SEI film also severely affects the charge distribution on the electrode surface, exacerbating the lithium dendrite growth problem. + The inhomogeneity of deposition and stripping further leads to uneven nucleation and growth of lithium, forming dendrites such as filamentous lithium and moss-like lithium. The growth of lithium dendrites not only reduces battery capacity and efficiency but can also puncture the separator and cause internal short circuits, leading to serious safety issues. Furthermore, lithium dendrites may detach from the substrate during growth, forming so-called "dead lithium." Dead lithium covers the lithium metal electrode, hindering lithium-ion transport and reducing battery capacity.
[0005] Currently, domestic and international scientists have conducted extensive research and proposed various types of additives to address the aforementioned problems. Xiong (Xiong X, et al. Dual-Interface Regulation of Cyclic Thioether Electrolyte Additives for Enhancing the Cycling Stability of High-Voltage Lithium Metal Batteries [J]. Small, 2025, 21, e07802.) et al. proposed using 1,4-dithiane (1,4-DH) as a multifunctional cyclic sulfide additive for carbonate electrolytes. This additive can preferentially adsorb and decompose on the lithium metal anode surface, constructing a dense SEI film rich in LiF and Li2S, significantly inhibiting lithium dendrite growth and improving overall battery performance. However, the solubility of 1,4-DH additive in carbonate electrolytes is limited (≤3.0 wt%), and it is prone to side reactions at higher voltages. Zhang (Zhang L, et al. A fluorine rich borate ionic additive enabling high-voltage Li metal batteries[J]. Energy Storage Materials, 2024, 69,103397.) et al. reported a lithium tetratetra(perfluoro-tert-butoxy)borate additive (Li TFOB can be reduced at the lithium anode; its single molecule contains 36 F atoms, thus it can generate LiF and Li-rich compounds. B O's SEI effectively reduces battery polarization and improves coulombic efficiency; however, the cost of this additive molecule and its dosage (5.0 wt%) are relatively high, which greatly limits its subsequent practical application.
[0006] Therefore, to efficiently address the issues of side reactions in the lithium anode electrolyte and lithium dendrite growth, it is necessary to further develop low-cost, high-efficiency electrolyte additives to optimize the chemical composition and microstructure of the lithium anode SEI, while simultaneously improving its Li- content. + Transmission efficiency and mechanical properties. Summary of the Invention
[0007] The purpose of this invention is to provide a lithium metal battery electrolyte containing ammonium-based strong polar cationic additives, which effectively solves the problems inherent in lithium anodes and provides a reference for the design and modification of lithium anode interfaces.
[0008] The objective of this invention is achieved through the following technical solution: In a first aspect, the present invention relates to an additive for a lithium battery electrolyte, the additive being composed of a highly polar, large-volume ammonium cation and a fluorine-containing anion, wherein the cation is a 4-fluorophenylammonium cation and the anion is BF4. - Anions.
[0009] As one embodiment of the present invention, the additive preferentially adsorbs onto the surface of the lithium anode during the charging and discharging process, forming a benign electric double layer composed of a cation-modified inner Helmholtz layer and an anion-rich outer Helmholtz layer.
[0010] As one embodiment of the present invention, a dense and uniform SEI is formed during the charging and discharging process, which is mainly composed of LiF and Li3N components.
[0011] In a second aspect, the present invention relates to a lithium battery electrolyte, wherein the electrolyte is composed of an organic carbonate solvent, a lithium salt, and the aforementioned additives.
[0012] As one embodiment of the present invention, the organic carbonate solvent is composed of cyclic carbonate and chain carbonate solvents in a volume ratio of 1:1 to 3:7.
[0013] In one embodiment of the present invention, the organic carbonate solvent is an EC (ethylene carbonate) / DEC (diethyl carbonate), FEC (fluoroethylene carbonate) / FEMC (methyltrifluoroethyl carbonate), or EC / EMC (methyl ethyl carbonate) system. The FEC / FEMC system is preferred.
[0014] In one embodiment of the present invention, the lithium salt is one or more selected from LiPF6, LiTFSI (lithium bis(fluorosulfonyl)imide), and LiFSI (lithium bis(fluorosulfonyl)imide). LiPF6 is preferred.
[0015] In one embodiment of the present invention, the lithium salt concentration in the electrolyte is 1-1.5 mol / L. -1 .
[0016] In one embodiment of the present invention, the concentration of the additive in the electrolyte is 0.01-0.05 mol / L. -1 0.02 mol L is preferred. -1 .
[0017] Thirdly, the present invention relates to a lithium metal battery, wherein the lithium metal battery uses the lithium battery electrolyte described in any of the preceding claims.
[0018] In some specific implementation examples, a certain amount of 4-fluorophenylammonium tetrafluoroborate is mixed with 1 mol / L of water according to the target concentration. -1A LiPF6FEC:FEMC (volume ratio 3:7) system, after mixing and stirring to dissolve, can be used as an electrolyte for lithium metal batteries. The target concentration range is 0.01-0.05 mol / L. -1 Between, preferably 0.02 mol L -1 .
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The 4-fluorophenylammonium cation in the additive used in this invention contains nitrogen and fluorine elements, is positively charged and has strong polarity, and can be quickly adsorbed on the lithium metal surface. At the same time, its large volume can reduce the proportion of solvent molecules in the double layer at the lithium anode / electrolyte interface, which is conducive to the formation of nitrogen-containing and fluorine-rich SEI and reduces unnecessary electrolyte consumption.
[0020] (2) The additives used in this invention can exert their effects at a low dosage (0.02 mol L). -1 In 1 mol L -1 In the LiPF6FEC:FEMC (volume ratio 3:7) system, it is 0.27 wt%. It dissolves quickly, has no side reactions, and has a moderate cost, making it a potential candidate for further promotion and application.
[0021] (3) This invention provides a novel lithium battery electrolyte additive and offers new design ideas and research perspectives for lithium anode interface design and modification. Attached Figure Description
[0022] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 This is a schematic diagram illustrating the mechanism of action of the additive 4-fluorophenylammonium tetrafluoroborate. Figure 2 The constant current discharge specific capacity of Ni92||Li battery containing 4-fluorophenylammonium tetrafluoroborate is shown in the graph. Figure 3 Impedance plots of Li||Li batteries containing 4-fluorophenylammonium tetrafluoroborate at different temperatures after cycling; Figure 4 The specific capacity of Ni92||Li batteries containing 4-fluorophenylammonium tetrafluoroborate is plotted under different currents. Figure 5 This is a SEM image of the lithium anode surface after cycling in a Ni92||Li battery containing 4-fluorophenylammonium tetrafluoroborate. Figure 6 This is a SEM cross-sectional image of the lithium anode of a Ni92||Li battery after cycling, containing 4-fluorophenylammonium tetrafluoroborate. Figure 7The constant current discharge specific capacity diagram of Ni92||Li battery; Figure 8 Impedance plots of Li||Li batteries at different temperatures after cycling; Figure 9 SEM image of the lithium anode surface after cycling in a Ni92||Li battery; Figure 10 SEM cross-sectional image of the lithium anode after cycling in a Ni92||Li battery; Figure 11 The specific capacity of Ni92||Li batteries under different currents is shown in the graph. Figure 12 This is a comparison chart of the constant current discharge specific capacity of Ni92||Li batteries containing 4-fluorophenylammonium tetrafluoroborate, NH4BF4, and without additives. Detailed Implementation
[0023] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.
[0024] Example 1 Using Ni92 cathode material (LiNi) 0.92 Co 0.04 Mn 0.04 O2 was used as the positive electrode active material, and mixed with a conductive agent (Super P) and a binder (PVDF) in a mass ratio of 90:5:5. The mixture was coated onto aluminum foil to a thickness of 100 μm, dried, and then cut into Ni92 positive electrode sheets with a diameter of 12 mm. The active material loading was between 2.5-3.5 g / sheet. Simultaneously, a lithium metal sheet with a purity of 99.9%, a diameter of 16 mm, and a thickness of 0.5 mm was used as the negative electrode. A polypropylene (PP) membrane with a thickness of 25 μm and a porosity of 55% was used as the separator, containing 0.02 mol / L of active material per 60 μL. -1 1 mol L of 4-fluorophenylammonium tetrafluoroborate -1 LiPF6FEC:FEMC (volume ratio 3:7) was used as the electrolyte to assemble Ni92||LiCR2O32 coin cells. The cells were tested at 0.1 C (1 C = 210 mAh g⁻¹). -1 After activation by constant current charge-discharge at 2.8-4.3 V and 25 ℃ for 2 cycles, the initial discharge specific capacity at 1 C current is 191 mAh g. -1 After 500 cycles, the discharge specific capacity is 139 mAh g. -1The capacity retention rate was 73%. Figure 2 The mechanism of action of the additive 4-fluorophenylammonium tetrafluoroborate is as follows: Figure 1 As shown.
[0025] Example 2 Using the aforementioned lithium metal sheet as the negative electrode and a PP membrane as the separator, 30 μL contains 0.02 mol / L... -1 1 mol L of 4-fluorophenylammonium tetrafluoroborate -1 Symmetric Li||LiCR2016 coin cells were assembled using LiPF6FEC:FEMC (volume ratio 3:7) electrolyte. The cells underwent one 1-hour charge-discharge cycle at 25 °C and 1 mA, followed by 50 charge-discharge cycles at 2 mA, with each charge and discharge cycle lasting 1 hour. Electrochemical impedance spectroscopy (EIS) tests were performed at 10 °C, 20 °C, 30 °C, 40 °C, and 50 °C using an electrochemical workstation. Figure 3 The testing frequency is 0.1-10. 5 Hz.
[0026] Example 3 Using the aforementioned Ni92 positive electrode as the positive electrode, a lithium metal sheet as the negative electrode, and a PP film as the separator, 60 μL contains 0.02 mol / L... -1 1 mol L of additive -1 Ni92||LiCR2O32 coin cells were assembled using LiPF6FEC:FEMC (3:7) as the electrolyte. The cells were subjected to 5 charge-discharge cycles at 0.2 C, 0.5 C, 1 C, 2 C, and 4 C respectively. Figure 4 The discharge specific capacity at 0.2 C current is 215 mAh g. -1 The discharge specific capacity at 4 C current is 174 mAh g. -1 .
[0027] Figure 5 This is a SEM image of the lithium anode surface after cycling in a Ni92||Li battery containing 4-fluorophenylammonium tetrafluoroborate. Figure 6 This is a SEM cross-sectional image of the lithium anode after cycling in a Ni92||Li battery containing 4-fluorophenylammonium tetrafluoroborate; Figure 5 , Figure 6 It can be seen that after adding the additive, the SEI interface layer generated on the surface of the lithium anode is more dense and uniform with a thickness of about 6.2 μm, indicating that the interface impedance of the system is low and effectively prevents the side reaction between the lithium anode and the electrolyte.
[0028] Comparative Example 1 Using the aforementioned Ni92 positive electrode as the positive electrode, lithium metal sheet as the negative electrode, and PP film as the separator, 60 μL 1mol L -1 LiPF6FEC:FEMC (3:7) was used as the electrolyte to assemble Ni92||LiCR2O32 coin cells. The cells were tested at 0.1 C (1 C = 210 mAh g⁻¹). -1 After activation by constant current charge-discharge at 2.8-4.3 V and 25 ℃ for 2 cycles, the initial discharge specific capacity at 1 C current is 175 mAh g. -1 After 500 cycles, the discharge specific capacity is 114 mAh g. -1 The capacity retention rate is 65% ( Figure 7 ).
[0029] Comparative Example 2 use The above Lithium metal sheet as the negative electrode, PP membrane as the separator, 30 μL 1 mol L -1 Symmetric Li||LiCR2016 coin cells were assembled using LiPF6FEC:FEMC (volume ratio 3:7) electrolyte. After completing one 1-hour charge-discharge cycle at 1 mA, the cells were subjected to 50 charge-discharge cycles at 2 mA, with each charge and discharge cycle lasting one hour. Following cycling, electrochemical impedance spectroscopy was performed at 10℃, 20℃, 30℃, 40℃, and 50℃ using an electrochemical workstation. Figure 8 The testing frequency is 0.1-10. 5 Hz.
[0030] Comparative Example 3 Using the aforementioned Ni92 positive electrode as the positive electrode, lithium metal sheet as the negative electrode, and PP film as the separator, 1 mol L - 1 Ni92||Li batteries were assembled using LiPF6FEC:FEMC (volume ratio 3:7) as the electrolyte. The batteries were subjected to 5 charge-discharge cycles at 0.2 C, 0.5 C, 1 C, 2 C, and 4 C, respectively. Figure 11 The discharge specific capacity at 0.2 C current is 196 mAh g. -1 The discharge specific capacity at 4 C current is 160 mAh g. -1 .
[0031] Figure 9 This is a SEM image of the lithium anode surface after cycling in a Ni92||Li battery. Figure 10 This is a SEM cross-sectional image of the lithium anode after cycling in a Ni92||Li battery; from Figure 5 , Figure 6 and Figure 9 , Figure 10The comparison shows that the SEI interface layer formed on the surface of the lithium anode in the additive-free system has a rough and uneven morphology with a thickness of about 28 μm, indicating that the system has a high interfacial impedance and that the lithium anode and electrolyte produce more intense side reactions.
[0032] Comparative Example 4 Using the aforementioned Ni92 positive electrode as the positive electrode, a lithium metal sheet as the negative electrode, and a PP film as the separator, 60 μL contains 0.02 mol / L... -1 Ni92||LiCR2O32 coin cells were assembled using 1 mol L⁻¹ LiPF₆ FEC:FEMC (3:7) with NH₄BF₄ additive as the electrolyte. After two cycles of constant current charge-discharge activation at 0.1 C (1 C = 210 mAh g⁻¹), 2.8–4.3 V, and 25 °C, the initial discharge specific capacity at 1 C was 176 mAh g⁻¹. -1 After 150 cycles, the discharge specific capacity is 147 mAhg. -1 The capacity retention rate was 84%. Figure 12 Comparison of test results with those of systems containing 4-fluorophenylammonium tetrafluoroborate and those without additives shows that the NH4BF4 additive can achieve a similar effect on improving battery performance as 4-fluorophenylammonium tetrafluoroborate, but its contribution to battery performance improvement is not as significant as that of 4-fluorophenylammonium tetrafluoroborate. Other additives, such as tetraethylammonium tetrafluoroborate, share similarities with NH4BF4: they are all nonpolar ammonium salt cations containing four identical groups, with similar overall structures. Therefore, it can be inferred that tetraethylammonium tetrafluoroborate should also have a similar effect, but its impact on battery performance improvement is still limited compared to 4-fluorophenylammonium tetrafluoroborate.
[0033] In summary, this invention provides a lithium metal battery electrolyte containing an ammonium-based highly polar cation additive. This additive consists of a highly polar, bulky ammonium-based cation and a fluorine-containing anion, preferably 4-fluorophenylammonium tetrafluoroborate. During charge and discharge, this additive preferentially adsorbs onto the lithium anode surface, forming a benign electrical double layer composed of a cation-modified inner Helmholtz layer and an anion-rich outer Helmholtz layer, and promotes the formation of a LiF and Li3N-rich SEI film; the thickness of this SEI layer is approximately 5-10 μm, and its impedance at room temperature is approximately 40-80 Ω. When used in a lithium metal battery electrolyte, this additive can improve the battery's cycle life and rate performance. The additive of this invention has good compatibility with commercial electrolytes and is simple to process, providing a new reference for interface control in high-energy-density lithium batteries.
[0034] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A lithium battery electrolyte additive, characterized in that, The additive consists of a highly polar, large-volume ammonium cation and a fluorine-containing anion, wherein the cation is a 4-fluorophenylammonium cation and the anion is BF4. - Anions.
2. The lithium battery electrolyte additive according to claim 1, characterized in that, The additive preferentially adsorbs onto the surface of the lithium anode during charging and discharging, forming a benign electric double layer composed of a cation-modified inner Helmholtz layer and an anion-rich outer Helmholtz layer.
3. The lithium battery electrolyte additive according to claim 2, characterized in that, During the charging and discharging process, a dense and uniform SEI is formed, which is mainly composed of LiF and Li3N components.
4. A lithium battery electrolyte, characterized in that, The electrolyte is composed of an organic carbonate solvent, a lithium salt, and the additive described in claim 1.
5. The lithium battery electrolyte according to claim 4, characterized in that, The organic carbonate solvent is composed of cyclic carbonate and chain carbonate solvents in a volume ratio of 1:1 to 3:
7.
6. The lithium battery electrolyte according to claim 4 or 5, characterized in that, The organic carbonate solvent is a compound system of ethylene carbonate (EC) and diethyl carbonate (DEC), a compound system of fluoroethylene carbonate (FEC) and methyl trifluoroethyl carbonate (FEMC), or a compound system of ethylene carbonate (EC) and methyl ethyl carbonate (EMC).
7. The lithium battery electrolyte according to claim 4, characterized in that, The lithium salt is one or more of LiPF6, LiTFSI, and LiFSI.
8. The lithium battery electrolyte according to claim 4, characterized in that, The lithium salt concentration in the electrolyte is 1-1.5 mol / L. -1 .
9. The lithium battery electrolyte according to claim 4, characterized in that, The concentration of the additive in the electrolyte is 0.01-0.05 mol / L. -1 .
10. A lithium metal battery, characterized in that, The lithium metal battery uses the lithium battery electrolyte as described in any one of claims 4-9.